Faecal waste collection practices performance of sanitation service chain in Marsabit town; Marsabit county, Kenya - Ali, Mohamed (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Much of the evidence linking latrine promotion to improved sanitation focuses on reporting the size of short-term treatment effects rather than long-term impacts (Kim et al., 2017). While the literature focuses on latrine adoption, few studies evaluate sustained latrine use, even though the use of latrine is essential to achieve health benefits (Cairncross et al., 2016).. A cross sectional descriptive study design was employed for the study. Both qualitative and quantitative data were collected. The study majorly described the safely managed faecal waste and unsafely managed faecal waste in Marsabit town for the purpose of public health planning. Data was collected on individual characteristics by identifying the sources of water and types of toilets residents of Marsabit used for their daily activities. The study design aided the researcher to comprehensively understand the exposure risk factors to sanitation related illnesses that residents of Marsabit faced as they used their toilets. Sampling design of simple random was used to select the participants within the zones of Marsabit town and enabled each member of the population an equal chance of being selected. Qualitative was carried out using audio recording and duly-filled questionnaires. The recordings of respondent voice were transcribed into written texts and the data was compared with notes written by research assistants. Quantitative data collected at the households was analyzed using the descriptive statistics in SPSS version 25. Descriptive data was presented in tables. Out of total 612 Marsabit town respondents 18.79% (n=115) of participants used flushed to pit latrine, 24.02% (n=147) used ventilated and improved pit latrine, Pit latrine which contain slab was the preferred method of waste collection at 31.86% (n=195), 14.87% (n=91) used open pit, 1.47% (n=9) used composting toilet, 5.72% (n=35) used hanging toilet, and 3.27% (n=20) of participants had no toilet facility. Pit latrine with slab constitute highest classification of waste disposal 31.86% (n=195) followed by Ventilated improved pit latrine at 24.02% (n=147). waste collection practice along sanitation service chain was indirectly and directly influenced by economic status of the community for safe management and disposal. This community practice pit latrine with slab as the main form of waste collection at 31% (n=195). improved social economic status of the community through economic growth and wealth creation will improve effective waste collection practices along service chain.